Localizing immersion education: A case study of an international bilingual education program in south China. Issue 9 (20th October 2020) - Xiong, Tao; Feng, Anwei
ABSTRACT: Due to the growing status of English as the language of international communication, English immersion programs have been on the rise in China and the rest of the world. Though there has been much discussion on the theoretical and practical characteristics and features of immersion, current models are not adequate for explaining the language-driven English immersion programs in the English as a Foreign Language (EFL) context such as China. Drawing on interviews, observations and documentary data and test scores gathered during a longitudinal study of a public-funded foreign languages school in China, this paper reports on a Sino-Canadian collaborative educational program and concludes that in addition to exhibiting most of the core features of immersion programs suggested by Swain and Johnson (1997 ), the program revealed several noteworthy emerging characteristics. The study argues for the importance of re-contextualizing Swain and Johnson's model of immersion to address the local social, cultural and educational contexts as more and more schools are adopting this model of language-driven bilingual education in China.